FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEKURANGAN ENERGI KRONIK (KEK) PADA IBU HAMIL DI PUSKESMAS BELIMBING PADANG TAHUN 2016 - Laila Rahmi (Jurnal Kesehatan Medika Saintika, 2017)
Chronic Energy Deficiency (CED) is a condition of pregnant women who suffer from long-lasting food shortages with various health problems (Sayogo, 2007). An increase in the incidence of CED in pregnant women from the year 2013 (4.4%) to 2014 (4.9%) (Padang City Health Office). The purpose of this research is to know the factors related to CED in pregnant women at Puskesmas Belimbing Padang in 2016. This type of research is analytical with cross sectional design, conducted at Puskesmas Belimbing Padang in February until September 2016. Population is all pregnant women in Puskesmas Belimbing Padang with sample 42 people taken using consecutive sampling technique. Data were analyzed by univariate and bivariate using chi square test. More than half of pregnant women experience CED, have low incomes, and age at risk, and less than half of pregnant women with risky parity and with risky gestational distance. There is a relationship between family income, age, parity, and distance pregnancy with CED in pregnant women